Manajemen Kurikulum Pendidikan Islam Pondok Tahfidz Wadil Qur'an Tangerang - Agung , AGUNG PRASETYO (Penerbit Minhaj Pustaka, 2025)
This research was conducted as an effort to determine the implementation of Islamic education curriculum management at Pndok Tahfizh Wadil Quran Tangerang. The aim of this research is to determine the implementation of curriculum management in Islamic Education at Pondok Tahfizh Wadil Quran Tangerang. This type of research is qualitative research with a descriptive approach. The data collection process is through interviews and observation. The results of this research explain that the curriculum management at Pondok Tahfizh Wadil Koran Tangerang is in accordance with the indicators of Islamic education curriculum management, carried out as follows: 1) Analysis of Islamic education curriculum management, 2) Islamic education curriculum planning process 3) organization of the Islamic education curriculum, 4) Implementation of the Islamic education curriculum, 5) Evaluation of the Islamic education curriculum. It was concluded that in general Pondok Tahfizh Wadil Quran Tangerang had implemented Islamic education curriculum management in accordance with Islamic curriculum management